Handbook of Research on Comparative Human Resource Management 2018
DOI: 10.4337/9781784711139.00016
|View full text |Cite
|
Sign up to set email alerts
|

Comparing performance management across contexts

Abstract: Comparing performance management across contexts 169 the public sector context. As performance management has been expanding in these new directions, what does this mean for its linkage with other aspects of the HRM system? PERFORMANCE MANAGEMENT AND HRMPerformance management is often seen as a microcosm of HRM, transferring the broader debate around the added value of human resource management to the performance management arena (Bach, 2000;Dewettinck, 2008). Special attention in both areas (HRM and performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Performance management is a company's method of evaluating, coaching, and developing personnel on a regular basis with the ultimate objective of improving organisational performance (in this case, creative behaviour) (Gorman, Meriac, Roch, Ray, & Gamble, 2017). Conducting evaluation interviews between line managers and subordinates is the most prevalent type of performance management (Boselie, Farndale, & Paauwe, 2018). Specific performance management needs develop as a result of the objective of promoting creative behaviour.…”
Section: Green Compensation and Employee Innovative Work Behaviourmentioning
confidence: 99%
“…Performance management is a company's method of evaluating, coaching, and developing personnel on a regular basis with the ultimate objective of improving organisational performance (in this case, creative behaviour) (Gorman, Meriac, Roch, Ray, & Gamble, 2017). Conducting evaluation interviews between line managers and subordinates is the most prevalent type of performance management (Boselie, Farndale, & Paauwe, 2018). Specific performance management needs develop as a result of the objective of promoting creative behaviour.…”
Section: Green Compensation and Employee Innovative Work Behaviourmentioning
confidence: 99%
“…In a review of research specifically on PA and merit pay, the U.S. National Research Council suggested that the economic environment could play an important role in determining the way organizations link PA and decisions about pay, by limiting or making available financial resources to support effective merit pay plans (Milkovich & Wigdor, 1991). In a recent comparison of performance management across contexts, Boselie, Farndale, and Paauwe (2018) highlight a decrease in some performance management related activities which they suggest may be reflective of the recent global financial crisis, a trend which for them highlights “the impact of external economic factors on the shaping of performance management in organizations” (p. 180).…”
Section: Dimensions Of Distal Context and Hypothesis Developmentmentioning
confidence: 99%
“…They call for further cross-national research into performance management. Boselie, Farndale, and Paauwe (2018) provide empirical data on performance management from the Cranet survey and their Global HRM Research Alliance study of 16 MNEs. Overall, they found that appraisal systems prevailed, particularly for clerical and manual workers.…”
Section: National Contextmentioning
confidence: 99%
“…LMEs are based on competition between and within firms, the assumption that government should play only a limited role, and a focus on short-term results for business owners. This context is likely to be more suited to individual targets and performance-based rewards (Boselie, Farndale, & Paauwe, 2018;Marsden, 2007). In CMEs, firms collaborate more -with each other and with government, and firms are more supported and/or restricted by legislation, and are required to focus on survival and the long-term interests of a wider group of stakeholders (Wood et al, 2014;Jackson & Deeg, 2019).…”
Section: Performance Appraisal and Comparative Capitalismsmentioning
confidence: 99%